Methods of micro-level analysis for agricultural programmes and policies : (Food and Agriculture Organization of the United Nations, 1994)
This publication represents the second series. Agricultural policy analysts require better ways of tailoring and targeting policy instruments and agricultural programmes to the actual circumstances of farm-households and rural communities. The overall objective of this document is to improve agricultural polices and programmes though the better use of micro-level analytical methods. Common methods are compared and contrasted for the benefit of those who manage agricultural policy analysis in developing countries